2019
DOI: 10.1039/c8nr05575k
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial biofilm destruction by size/surface charge-adaptive micelles

Abstract: Biofilms formed by pathogenic bacteria are one of the most important reasons for multidrug resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 37 publications
1
54
0
Order By: Relevance
“…In fact, a number of studies have reported enhanced antibiolm effect via bacterial lipase-triggered release of antibiotics. 73,74 Proteomic proling…”
Section: Antibacterial and Antibiolm Assaysmentioning
confidence: 99%
“…In fact, a number of studies have reported enhanced antibiolm effect via bacterial lipase-triggered release of antibiotics. 73,74 Proteomic proling…”
Section: Antibacterial and Antibiolm Assaysmentioning
confidence: 99%
“…Only a few of PSs are capable to contact with bacteria in biofilms, resulting in limited effectiveness . What is more, the encapsulation of EPS induces lack of oxygen in biofilms . The photodynamic efficiency of PS is further restricted by the hypoxia environment.…”
Section: Introductionmentioning
confidence: 99%
“…Similar idea was embodied in the work of Li et al, who designed size/surface charge adaptive micelles for drug delivery [ 35 ]. Antibiotic azithromycin was conjugated with block copolymers composed of PEG and poly (aspartamide) (PAsp), which self-assembled into micelles with positively charged surfaces.…”
Section: Nanocarriers Responsive To Bacterial Productsmentioning
confidence: 89%